A review of natural fibers and processing operations for the production of binderless boards - Tajuddin, Maisarah; Ahmad, Zuraida; Ismail, H. (North Carolina State University, 2016)
Decreasing wood supplies and the need for formaldehyde-free particleboard have become important issues. This has led to studies about the use of raw materials other than wood, along with the manufacture of particleboard without using any synthetic adhesives. This paper presents an overview of the development of binderless boards from natural fibers using a diverse range of manufacturing processes, such as heat and steam treatments. The features of binderless boards produced with various parameters, such as pressing parameters, particle sizes, and additional substances, under various manufacturing processes, are discussed. Based on the availability of natural fibers, binderless boards are typically evaluated for their physical, mechanical, and thermal properties. This review is approached with an understanding of the processes and contributing factors in producing binderless boards, helping to overcome some critical issues that are necessary for the development of future new "green" binderless boards through value-addition to enhance their usage.